Pengaruh Penggunaan Modul IPA Berbasis Problem Based Learning (PBL) Terhadap Keterampilan Proses Sains Dan Keterampilan Berpikir Kritis Siswa (The Effect of Using Problem Based Learning (PBL) Natural Sciences Modules on Students' Science Process Skills a - Aulia, Rizky Eka; Sumiharsono, Rudy; Triwahyuni , Eges (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study was to find out whether using the Problem Based Learning (PBL) module can improve (PBL) Science Process Skills and Students' Critical Thinking Skills. Research design: causal quantitative, determination of research area: purposive sampling area, determination of respondents: population research area. Data collection: 1). observation, 2). interview, 3). document. Data analysis 1) instrument test, 2) classic assumption test, 3) hypothesis test. Based on the results of the F-test analysis, it can be decided that the significance level is 0.001 or less than 0.05 and the F-count value is greater than the F-table (3.367 > 2.901). According to Mulyono (2018: 113), it can be decided that H0 is rejected so that it can be taken the conclusion that the independent variable has a significant influence on the dependent variable. This means that it can be concluded that there is an effect of using the Problem Based Learning module (variable X) on science process skills (variable Y1) and critical thinking skills (variable Y2) jointly with class X SMK PGRI Sempu in the even semester of the 2022/2023 academic year. So it can be concluded that the Problem Based Learning (PBL) Module has an effect on Science Process Skills and Students' Critical Thinking Skills and H0 is rejected.